Structural characterization of human de novo protein NCYM and its complex with a newly identified DNA aptamer using atomic force microscopy and small-angle X-ray scattering - Yamamoto, Seigi; Kono, Fumiaki; Nakatani, Kazuma; Hirose, Miwako; Horii, Katsunori; Hippo, Yoshitaka; Tamada, Taro; Suenaga, Yusuke; Matsuo, Tatsuhito (Frontiers in Oncology, 2023)
NCYM, a Homininae-specific oncoprotein, is the first de novo gene product experimentally shown to have oncogenic functions. NCYM stabilizes MYCN and b-catenin via direct binding and inhibition of GSK3b and promotes cancer progression in various tumors. Thus, the identification of compounds that binds to NCYM and structural characterization of the complex of such compounds with NCYM are required to deepen our understanding of the molecular mechanism of NCYM function and eventually to develop anticancer drugs against NCYM. In this study, the DNA aptamer that specifically binds to NCYM and enhances interaction between NCYM and GSK3b were identified for the first time using systematic evolution of ligands by exponential enrichment (SELEX). The structural properties of the complex of the aptamer and NCYM were investigated using atomic force microscopy (AFM) in combination with truncation and mutation of DNA sequence, pointing to the regions on the aptamer required for NCYM binding. Further analysis was carried out by small-angle X-ray scattering (SAXS). Structural modeling based on SAXS data revealed that when isolated, This is a provisional file, not the final typeset article NCYM shows high flexibility, though not as a random coil, while the DNA aptamer exists as a dimer in solution. In the complex state, models in which NCYM was bound to a region close to an edge of the aptamer reproduced the SAXS data. Therefore, using a combination of SELEX, AFM, and SAXS, the present study revealed the structural properties of NCYM in its functionally active form, thus providing useful information for the possible future design of novel anti-cancer drugs targeting NCYM.